Meningkatkan Mutu Layanan Perguruan Tinggi Melalui Praktik Pengelolaan Quality Work of Life Karyawan - Ratna Widiastuti; Meily Margaretha (Conference In Business, Accounting, And Management (CBAM), 2012)
Giving the best quality service to the students is the purpose of many education institutions. One of the factors that support the service is employees who work in the organization, which are lecturer and employee support system. Therefore, employees should be motivated in order to improve their performance. Quality work of life is a concept that supports the quality work of the employee in the organization. This concept tries to improve employees’ dignity and self esteem. The important role of quality work of life is to change the work climate of the organization in order create a better work of life. The purpose of this paper is to give a conceptual review of quality work life with its practices in organization, such as financial compensation, carrier opportunity, and job characteristics.Keywords: higher education, service quality, quality work of life